2021
DOI: 10.1002/anie.202104051
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of the Archaeal Lipid Parallel GDGT‐0 (Isocaldarchaeol)**

Abstract: Archaeal glycerol dibiphytanyl glycerol tetraethers (GDGT) are some of the most unusual membrane lipids identified in nature.T hese amphiphiles are the major constituents of the membranes of numerous Archaea, some of which are extremophilic organisms.D ue to their unique structures, there has been significant interest in studying both the biophysical properties and the biosynthesis of these molecules. However,these studies have thus far been hampered by limited access to chemically pure samples.Herein, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 105 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Scheme a shows the syntheses of archaeal lipids 1 and 2 . Some synthetic routes to the archaeal lipids and their related lipids, including chemical synthesis and semisynthesis, , have been reported. One of the critical steps toward their syntheses is a β-selective glycosylation between sugars and archaeol 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Scheme a shows the syntheses of archaeal lipids 1 and 2 . Some synthetic routes to the archaeal lipids and their related lipids, including chemical synthesis and semisynthesis, , have been reported. One of the critical steps toward their syntheses is a β-selective glycosylation between sugars and archaeol 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In earlier work led by the Burns group, an efficient synthetic route to the core structure of parallel GDGT-0 (iso-caldarchaeol) was described. 19 In the same work, the synthesis of P2 and P1Glc were reported. In this work, along with P2 and P1Glc, the synthesis of two additional GDGT lipids -PG2 and PG1Glc was achieved (Figure 2, Supplementary Schemes S1-7).…”
Section: Figurementioning
confidence: 92%
“…Differential scanning calorimetry (DSC) studies on bulk GDGT lipid mixtures from extracts typically revealed that the lipids exist in fluid phases at all temperatures and do not exhibit any endothermic phase transitions. 19 However, it may be challenging to detect transitions like lamellar to hexagonal which are typically characterized by low enthalpy changes. 44 Moreover, each DSC measurement requires a significant amount of material that is not always practical to recover.…”
Section: Characterization Of Mesophases Formed By Gdgtsmentioning
confidence: 99%
See 1 more Smart Citation